A PHENOMENOLOGICAL STUDY ON ADOLESCENTS’ RESILIENCE IN FAMILY - Jia, Yi Tan; Kai , Yee Hon; Bee , Seok Chua; Mutang, Jasmine Adela (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Adolescence is a developmental stage characterized by profound physical, cognitive, emotional, and social transformations. Maintaining balanced mental health is especially important during this period, as it supports adolescents in navigating these challenges. This study employed a qualitative research approach to explore adolescents lived experiences of resilience, using Interpretative Phenomenological Analysis (IPA). A total of five adolescents, aged 16 to 17, participated in in-depth interviews. The thematic analysis revealed four key themes: (a) Family Dynamics and Conflict Response, (b) Adaptive Recovery from Family Conflicts, (c) Attribution in Family Conflicts, (d) Discipline and Moral Learning in Families, (e) Emotion-Focused Coping，and (f) Behavioural Coping in Family Stress. The findings highlight the central role of the family in shaping adolescents’ resilience, both as a source of challenges and as a foundation for coping strategies.